1079 Is PTSD In Young Women Associated With Rem Sleep Abnormalities?. (27th May 2020) - Martinez, D; Yeh, M; Oliveira, L; Coimbra, B; Mello, A F; Poyares, D; Tufik, S; Mello, M F
Abstract: Introduction: The increase in violence against young women has a high impact on the prevalence of Posttraumatic stress disorder (PTSD). The lifetime prevalence of PTSD is twice as high in women. However, most studies assessing sleep disturbances in PTSD were conducted predominantly in male samples and combat veterans. Objective: To analyze the sleep of young women with and without PTSD. Hypothesis: Women with PTSD have worse sleep quality, higher arousability, and higher muscle activity during REM sleep. Methods: Case-controlled study with young women. Seventy-four women who suffered sexual assault and developed PTSD (DSM-5); and 64 women from the community without PTSD. Women were recruited from the PTSD outpatient clinic (Universidade Federal de São Paulo, Brazil).Clinician-Administered Posttraumatic Stress Scale (CAPS 5), Beck Depression and Anxiety Inventories (BDI) (BAI), full in-lab Polysomnography (PSG), Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Índex (PSQI), Fatigue Impact Scale (FIS), and Insomnia Severity Índex (ISI) were applied to all participants. Analysis of variance, regression models, and general linear modeling were used. Results: Patients mean age was 28 vs 24 for the control group (p=0.004). CAPS mean score in PTSD-group was 42.5±9.1. BDI, BAI, FIS, PSQI, ISI scores were worse in PTSD-group (p<0.05, all). Pittsburgh Sleep Quality Index (PSQI) score was significantly associated with CAPS 5 independently of depression, fatigue, and sleep fragmentation. The PTSD women had lower total sleep time (p= 0.01) and lower REM sleep percentage (p=0.04). However, the control group had higher arousal index (p=.0.01) and had higher muscle activity during REM sleep (p=0.03) than PTSD. Conclusion: Women with PTSD had significantly worse score in PSQI, FIS, and ISI. PSQI score was associated with PTSD severity. However, when PSG results are concerned, we found higher sleep fragmentation in the control group. We speculate that women with PTSD may have felt safer and taken care of in the lab, which might explain the difference between objective and subjective measures of sleep quality in PTSD. Support: Acknowledgments: FAPESP: Fundação de Apoio à pesquisa de São Paulo, AFIP: Associação Incentivo a Pesquisa